1987
DOI: 10.1007/bf02470596
|View full text |Cite
|
Sign up to set email alerts
|

The hypertrophic uncinate process of the pancreas wrapping the superior mesenteric vein and artery —A case report—

Abstract: The hypertrophic uncinate process of the pancreas wrapping the superior mesenteric vein and artery was discovered during surgery on a patient with nodular chronic pancreatitis. Such a rare anomaly has never been noted in the English literature so far as we have been able to find. This malformation of the pancreatic uncinate process was considered to be due to excess fusion between the ventral and dorsal pancreatic anlages during embryonic stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…The first case of a PAP was described by Sugiura et al in 1987, and two subsequent reports were published in 2001 and 2004. [1][2][3] However, to the best of our knowledge, no subsequent reports on the malformation appeared and little attention was devoted to its frequency or how it could potentially affect pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case of a PAP was described by Sugiura et al in 1987, and two subsequent reports were published in 2001 and 2004. [1][2][3] However, to the best of our knowledge, no subsequent reports on the malformation appeared and little attention was devoted to its frequency or how it could potentially affect pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have only been three reports of a PAP in the literature. [1][2][3] During pancreatic resection, the presence of a PAP significantly affects the procedure, including the pancreaticointestinal reconstruction. Thus, it is important to recognize a PAP preoperatively; however, the frequency and characteristics of the anomaly have yet to be precisely determined.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 At least six surgically confirmed cases have been reported in the English literature. [10][11][12][13][14][15] Recent retrospective studies of image records revealed an unexpectedly high incidence of this variant, 10 which highlights poor recognition of this entity. Circumportal pancreas is generally an innocuous and the diagnosis is usually made incidentally.…”
Section: Case Reportmentioning
confidence: 99%
“…The full-text articles of the remaining 281 studies were assessed for eligibility. Overall, 21 articles, including our own case, met the inclusion criteria and reported PAP in 59 patients in total 111,13,14,1723 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The uncinate remains its own pancreatic duct, the inferior branch of the pancreatic duct. Two different hypotheses are discussed regarding the development of PAP: either it is a malformation of the portal venous system 8,9 or the pancreas caused by hypertrophy of the ventral 10,11 or dorsal anlagen 3 and subsequent fusion to the left of the mesenteric or portal vein. This anatomic variant is well known from porcine pancreas 12 but described as rare in human, with a prevalence from 1.1% to 3.4% 1,8,13 in computed tomographic (CT) image studies of a healthy population 13 or of patients with hepatoma, adrenal or colon adenoma, uterine carcinoma, or pancreatic cyst, respectively.…”
mentioning
confidence: 99%